The Bible-- what is it? - MacRae, A. A.; Grauley, J. E.; Dunzweiler, R. J.; Newman, R. C.; Evans, F. W.; Harding, W. N.; Taylor, T. V.; Murray, J.; Laird, H. S. (Bible Evangelism, 1977)
No. 1. Revelation / A.A. MacRae -- no. 2. II Peter 1:21 / J.E. Grauley -- no. 3. Inerrancy and the Old Testament / A.A. MacRae -- no. 4. Inspiration / A.A. MacRae -- no. 5. Inspiration and inspiredness / R.J. Dunzweiler -- no. 6. Inerrancy and the synoptic problem / R.C. Newman -- no. 7. The battle for the Bible / F.W. Evans -- no. 8. Infallibility / W.N. Harding -- no. 9. John 17:17 / T.V. Taylor -- no. 10. Inerrancy and hermeneutics / T.V. Taylor -- no. 11. Issues and answers / J. Murray and H.S. Laird.